1976
DOI: 10.1037/0022-006x.44.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of therapists varying in community mental health ideology and democratic values.

Abstract: The purpose of Lhis study was to investigate the relationship between therapists' scores on the Community Mental Health Ideology Scale and the Democratic Values Scale and their ratings of patient ease histories on a number of altitudinal dimensions. Thirty-three therapists rated each of eight case histories of psychiatric outpatients on likabilily, comfort, interest in treating, interest in friendship, and prognosis. Patients' social class, diagnosis, and insight level were systematically varied within the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In nine (Briar, 1961;Efron, 1970;Haase, 1964;Kurtz et al, 1970;Lee & Temerlin, 1970;Levy & Kahn, 1970;Mintz, 1972;Stein et al, 1972;Trachtman, 1971) of the 14 analogue studies, less favorable clinical judgments were given to lower-as opposed to middle-class patients. Lower-class partisanship was found in three studies (Koscherak & Masling, 1972;Nalven et al, 1969;Routh & King, 1972), and equivocal or null results were obtained in two other studies (Amira et al, in press;Del Gaudio et al, 1976).…”
Section: Social Classmentioning
confidence: 90%
See 4 more Smart Citations
“…In nine (Briar, 1961;Efron, 1970;Haase, 1964;Kurtz et al, 1970;Lee & Temerlin, 1970;Levy & Kahn, 1970;Mintz, 1972;Stein et al, 1972;Trachtman, 1971) of the 14 analogue studies, less favorable clinical judgments were given to lower-as opposed to middle-class patients. Lower-class partisanship was found in three studies (Koscherak & Masling, 1972;Nalven et al, 1969;Routh & King, 1972), and equivocal or null results were obtained in two other studies (Amira et al, in press;Del Gaudio et al, 1976).…”
Section: Social Classmentioning
confidence: 90%
“…Clinician-subjects have included psychiatrists, clinical and school psychologists, social workers, nurses, psychiatric residents, clinical psychology interns and graduate students, and social work students. In seven (Amira et al, in press;Del Gaudio et al, 1976;Haase, 1964;Koscherak & Masling, 1972;Levy & Kahn, 1970;Nalven et al, 1969;Trachtman, 1971) of the 14 studies, the reported size of the professional (i.e., primarily nonstudent) sample was respectable. Subjects in three studies (Amira et al, in press;Levy & Kahn, 1970;Nalven et al, 1969) were drawn from nationally based professional organizations.…”
Section: Social Classmentioning
confidence: 99%
See 3 more Smart Citations